Pengaruh Total Asset Turn Over dan Debt to Asset Ratio Terhadap Return on Asset Pada Perusahaan Perhotelan, Restoran Dan Pariwisata yang Terdaftar di Bursa Efek Indonesia - Batubara, Hade Chandra; Ammy, Baihaqi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to determine and analyze the effect of Total Asset Turnover (TATO) and Debt to Asset Ratio (DAR) partially and simultaneously on Return on Assets (ROA) in the Hotel, Restaurant, and Tourism sub-sector companies listed on the Indonesia Stock Exchange. The population used in this study is 10 companies in the Hotel, Restaurant, and Tourism industry listed on the Indonesia Stock Exchange (IDX) from 2014 to 2017. From the above population, the author only decided on 9 companies as research samples. The data analysis techniques used are multiple linear regression, classical assumption test, t-test, F-test, and coefficient of determination. Partially, the Total Asset Turnover (TATO) variable shows a significant effect on Return on Assets (ROA) in the Hotel, Restaurant, and Tourism sub-sector companies listed on the Indonesia Stock Exchange. Partially, the Debt to Asset Ratio (DAR) variable shows a significant influence on Return on Assets (ROA) in the Hotel, Restaurant and Tourism sub-sector companies listed on the Indonesia Stock Exchange. Simultaneously, the Total Asset Turnover (TATO) and to Asset Ratio (DAR) variables show a significant influence on Return on Assets (ROA) in the Hotel, Restaurant and Tourism sub-sector companies listed on the Indonesia Stock Exchange. It is better to allocate debt as a source of funding for additional promotional costs and increased productivity which has an impact on the company's sales level. In order for the company's goals to be achieved, the company should be wiser in making funding decisions to use company debt. In order for the company to increase profitability, the company should manage net profit with the amount of capital and assets well so that the company is in a profitable state and condition.